DIGITAL TRANSFORMATION IN PESANTREN: IMPACTS AND CHALLENGES IN ISLAMIC EDUCATION - Maram, Ahmad Nabilul; Fanani, Zainal (Universitas Muhammadiyah Mataram, 2025)
This study explores the impact of digitalization on the teaching methods in Islamic boarding schools (pesantren), with a particular focus on the deterritorialization process through digital technology integration. In many cases, the digital approach is leveraged to complement traditional learning for alumni and external audiences who seek the spiritual atmosphere of the pesantren, while santri mukim (resident students) continue to learn directly under the guidance of a kiai in a dedicated religious environment (masjid or musala). The main aim of this research is to analyze how classical methods such as halaqah, sorogan, and bandongan are adapted to digital platforms. By employing qualitative case study methodology, the research identifies the benefits of digitalization, including enhanced access to education beyond the boarding environment, expanded reach of religious teachings, and increased participation in learning activities. However, the study also highlights persistent challenges faced by many pesantren in implementing digital tools, including low digital literacy, limited infrastructure, and resistance to change. This research contributes to the existing body of knowledge by demonstrating that selective integration of digital tools can enhance the relevance of pesantren for a broader community while retaining traditional values. To ensure the sustainability of digital transformation, the study suggests the need for improved digital literacy training, collaboration with technology providers, and clear governance policies. Future research should focus on how remote pesantren can address infrastructure limitations and investigate the long-term effects of digitalization on character development and religious understanding among both resident and non-resident students.